Comparative study of the essential oils of three Beilschmiedia species and their biological activities. (30th September 2015) - Salleh, Wan Mohd Nuzul Hakimi Wan; Ahmad, Farediah; Khong, Heng Yen; Mohamed Zulkifli, Razauden
Summary: This study was designed to examine the chemical compositions of the essential oils from three Beilschmiedia species and antioxidant, antimicrobial, antityrosinase, acetylcholinesterase and anti‐inflammatory activities. The essential oils of B. kunstleri, B. maingayi, B. penangiana gave β‐caryophyllene (10.6–12.1%), β‐eudesmol (17.5–24.1%) and δ‐cadinene (17.5–28.7%) as the most abundant components respectively. The bark oil of B. maingayi showed the highest activity in β‐carotene/linoleic acid (125.9%) and phenolic content (288.2 mg GA g −1 ), while B. penangiana bark oil was found to have strong activity in DPPH (IC50 84.7 μg mL −1 ) and ABTS (IC50 108.3 μg mL −1 ). The essential oils of B. penangiana showed the best activity against Candida glabrata with MIC value 31.3 μg mL −1 . The bark oil of B. penangiana gave 82.5% tyrosinase inhibiton. The leaf oil of B. maingayi gave the highest inhibition in AChE (66.6%) and lipoxygenase (77.0%) assay. Our findings demonstrate that the essential oils have great potential for applications in pharmaceutical and food industries. Abstract : Essential oils of three Beilschmiedia species are found to have strong antifungal and medium antioxidant, antityrosinase, anti‐inflammatory and acetylcholinesterase activities.